2021
DOI: 10.1097/ruq.0000000000000485
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Sound Touch Elastography, Sound Touch Quantify, and 4 Serum Fibrosis Indexes for the Diagnosis of Liver Fibrosis in Patients With Chronic Hepatitis B

Abstract: The aim of this research was to compare the use of shear wave elastography (sound touch elastography [STE] and sound touch quantify [STQ]) and serum liver fibrosis indexes in the evaluation and staging of chronic hepatitis B (CHB) liver fibrosis. Sound touch elastography is a form of 2-dimensional shear wave elastography, and STQ is a form of point shear wave elastography. Between June 2018 and March 2019, 122 patients with CHB were assessed using STE and STQ. Serum liver biomarkers tests were undertaken, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…A variety of methods have been developed to stage liver fibrosis in patients with chronic hepatitis B (CHB) (2); however, most of these methods are limited by complications or inaccuracies (3)(4)(5). The gold standard for liver fibrosis staging, liver biopsy, is an invasive method that can result in complications such as hemorrhage, infection, and pain (6,7), leading to patient reluctance in consenting to the procedure. Therefore, noninvasive methods such as liver ultrasound (US) and ultrasound elastography (USE) have been proposed as an alternative means of assessing liver fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of methods have been developed to stage liver fibrosis in patients with chronic hepatitis B (CHB) (2); however, most of these methods are limited by complications or inaccuracies (3)(4)(5). The gold standard for liver fibrosis staging, liver biopsy, is an invasive method that can result in complications such as hemorrhage, infection, and pain (6,7), leading to patient reluctance in consenting to the procedure. Therefore, noninvasive methods such as liver ultrasound (US) and ultrasound elastography (USE) have been proposed as an alternative means of assessing liver fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…14 The performance of STE and/or STQ in the staging of fibrosis in liver diseases of different etiologies has been evaluated. 12,[14][15][16][17][18][19] In a prospective multicenter study, Wang et al 14 demonstrated that STE and STQ detect liver stiffness reliably and are thus valuable for the noninvasive evaluation of liver fibrosis. Yang et al 15 recently reported that STE performs better than serological testing in the diagnosis and staging of liver fibrosis.…”
mentioning
confidence: 99%
“…The performance of STE and/or STQ in the staging of fibrosis in liver diseases of different etiologies has been evaluated 12,14–19 . In a prospective multicenter study, Wang et al 14 demonstrated that STE and STQ detect liver stiffness reliably and are thus valuable for the noninvasive evaluation of liver fibrosis.…”
mentioning
confidence: 99%